Venglustat, an orally administered glucosylceramide synthase inhibitor: Assessment over 3 years in adult males with classic Fabry disease in an open-label phase 2 study and its extension study - Patrick Deegan; Özlem Göker-Alpan; Tarekegn Geberhiwot; Robert J. Hopkin; Elena Lukina; Anna Tylki‐Szymańska; Atef Zaher; Charlotte Sensinger; Sebastiaan J.M. Gaemers; Vijay Modur; Beth L. Thurberg; Jyoti Sharma; et al. (2022)
Venglustat inhibits the enzymatic conversion of ceramide to glucosylceramide, reducing available substrate for the synthesis of more complex glycosphingolipids. It offers a potential new approach to the treatment of patients with Fabry disease (α-Gal A deficiency), in whom progressive accumulation of such glycosphingolipids, including globotriaosylceramide (GL-3), in the lysosomes of a wide range of cell types often leads to vital organ complications in adulthood. An international, open-label, single-arm, Phase 2a uncontrolled 26-week clinical study (NCT02228460) and a 130-week extension study (NCT02489344) were conducted to assess the safety, pharmacodynamics, pharmacokinetics, and exploratory efficacy of 15 mg once daily oral venglustat in treatment-naïve adult male patients with classic Fabry disease. Of 11 patients (18–37 years old) who initially enrolled, nine completed the 26-week study and seven completed the extension study. A total of 169 treatment-emergent adverse events (TEAEs) were reported by nine patients, the majority being mild (73%) and unrelated to the study drug (70%). Nine serious TEAEs (serious adverse events) and 11 severe TEAEs, including a self-harm event, were reported. No deaths or treatment-related life-threatening adverse events were reported. Skin GL-3 scores in superficial skin capillary endothelium (SSCE), estimated by light microscopy, were unchanged from baseline at Week 26 in five patients, decreased in three patients, and increased in one patient. There was no significant change in GL-3 scores or significant shift in grouped GL-3 scores. Five of six patients had reductions from baseline in GL-3 score at the end of the extension study. At Weeks 26 and 156 the mean (standard deviation) changes from baseline in the fraction of the volume of SSCE cytoplasm occupied by GL-3 inclusions, measured by electron microscopy unbiased stereology, were − 0.06 (0.03) (p = 0.0010) and − 0.12 (0.04) (p = 0.0008), respectively. Venglustat treatment reduced markers in the synthetic and degradative pathway of major glycosphingolipids; proximal markers reduced rapidly and more distal markers (plasma GL-3 and globotriaosylsphingosine) reduced progressively. There were no biochemical or histological indications of progression of Fabry disease over 3 years of follow-up. These findings confirm target engagement and the pharmacodynamic effects of venglustat in adult males with classic Fabry disease. However, further clinical evaluation in larger studies is needed to determine efficacy and safety.